Cosmovisión y celebración del mundo andino a través del ejemplo de la comunidad de Q'ero (Paucartambo) - Müller, Thomas (1984)
The Q'ero community is located in the heights of the limit of the provinces of Paucartambo and Quispicanchi, in the Department of Cusco. The territory covered by it -a total of 85,000 hectares-, reaches from 4,8000 meters. up to 1,800. The community is made up of about 500 people or 9 families (there are only 13 surnames!), who live in seven high altitude populations between 3,800 and 4,300 above sea level.